Heritage Revitalization Design Based on Gamification and AR Technology: A Case Study of the Old Library of Wuhan University - Han, Shiyu (Transactions on Environment, Energy and Earth Sciences, 2026)
In the context of the digital technology-enabled revitalization of cultural heritage, this study takes the Old Library of Wuhan University as the research subject. Drawing on existing research results such as the structural characteristics of its roof, and using AR technology as the core, it integrates gamification concepts and human-computer interaction design to explore innovative approaches to the revitalization and protection of individual historical buildings. The research will employ literature review, case analysis, and prototype design methods to construct a gamified interactive system based on AR technology. It is expected to enhance public awareness and protection consciousness of the Old Library of Wuhan University, improve the immersion and engagement of heritage experiences, and provide a practical model for the revitalization and protection of similar individual historical building heritage sites. Furthermore, by combining storytelling with interactive elements, the system aims to create an emotional connection between users and the building, fostering a deeper understanding of its historical significance and architectural value, thereby promoting sustainable cultural heritage preservation in the digital age.
Keywords: Gamification, Augmented reality, Heritage preservation.